2011
DOI: 10.1097/jcp.0b013e31820e3db6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aripiprazole Augmentation of Serotonin Reuptake Inhibitors or Clomipramine in Treatment-Resistant Obsessive-Compulsive Disorder

Abstract: Based on the evidence that aripiprazole added to serotonin reuptake inhibitors (SRIs) or clomipramine in treatment-resistant obsessive-compulsive disorder (OCD) has reported promising results, the present 16-week, double-blind, randomized, placebo-controlled trial had the aim to explore the efficacy of aripiprazole add-on pharmacotherapy on clinical symptoms and cognitive functioning in a sample of treatment-resistant OCD patients receiving SRIs. After clinical and neurocognitive assessments, patients were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 49 publications
3
78
2
2
Order By: Relevance
“…This can be explained by diverse pharmacological mechanisms of aripiprazole (25). Results of a double-blind, randomized, placebo controlled study supported the notion that adding aripiprazole to SSRIs could be a valid strategy for treatment-resistant OCD patients (26,27). Another study performed on 30 subjects provided evidences that aripiprazole augmentation of clomipramine treatment was well tolerated, and might be proposed as an effective therapeutic strategy to improve outcome in treatment-resistant OCD (27).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This can be explained by diverse pharmacological mechanisms of aripiprazole (25). Results of a double-blind, randomized, placebo controlled study supported the notion that adding aripiprazole to SSRIs could be a valid strategy for treatment-resistant OCD patients (26,27). Another study performed on 30 subjects provided evidences that aripiprazole augmentation of clomipramine treatment was well tolerated, and might be proposed as an effective therapeutic strategy to improve outcome in treatment-resistant OCD (27).…”
Section: Discussionmentioning
confidence: 62%
“…Results of a double-blind, randomized, placebo controlled study supported the notion that adding aripiprazole to SSRIs could be a valid strategy for treatment-resistant OCD patients (26,27). Another study performed on 30 subjects provided evidences that aripiprazole augmentation of clomipramine treatment was well tolerated, and might be proposed as an effective therapeutic strategy to improve outcome in treatment-resistant OCD (27). Successful treatment result in an OCD subject with treatment of escitalopram and aripiprazole proved that dopaminergic pathways might play an important role in OCD pathogenesis as well as serotonergic pathways, and that imbalance between these pathways might cause this disorder.…”
Section: Discussionmentioning
confidence: 64%
“…Aripiprazole has been studied in two positive double-blinded clinical trials and a single-blinded randomized study with results that favor the use of aripiprazole. [104][105][106] A meta-analysis by Dold et al 100 including a double-blinded study with aripiprazole reported that the results were inconsistent. Conversely, new Canadian clinical practice guidelines recommend the use of aripiprazole in addition to risperidone as first-line adjunctive therapy.…”
Section: Venlafaxinementioning
confidence: 99%
“…Data from multiple case series [52,53] and two placebo-controlled RCTs [21,54] have demonstrated the efficacy of aripiprazole augmentation in treatment-resistant OCD.…”
Section: Aripiprazolementioning
confidence: 99%